Rancang Bangun Sistem Pakar Identifikasi Penyakit Gigi Berbasis Web Dengan Menggunakan Metode Certainty Factor - Irfan, Mochammad; Irawan, Jusak; saskianti, Tania (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
This research is motivated by common dental diseases that are present among people. it is evident that people will visit dentist only when they experience serious problems with their teeth, this mainly because a lack of understanding against the dental disease and also expensive charge of dental checkup. therefore, in this study we build an application for diagnosing common dental disease. a web-based application that is available to be accessed freely. The purpose of this study is to build a expert system for identifying dental disease.The expert system utilized the certainty factor method as the inference engine. The reason behind this is  because this method is able to produce alternatives diagnosis (the output of the system comprises of some diagnosis results). It can be seen that certainty factor method is very suitable for expert system problem solving for disease diagnosis. This research was done by way of anamnesis process (giving a question to the user). The system produces a possibility of the diseases as well as causative factor and handling factor.This work has been tested by an expert using 30 times experiment. Based on our examination some result were obtained as follows: Firstly, the system gives similar results in reference  to the expert judgment of disease. Secondly, the system gives possibilities of the disease when we considered confidence level above 80%. Thirdly, the results were considered invalid when the diagnosis of the system didn’t match with the expert judgment